EFFECT OF GROWING MEDIA ON THE GROWTH OF Streptomyces sp. AND Trichoderma harzianum AS ANTHRACNOSE DISEASE BIOCONTROL - Rulinggar, Nia; Mujoko, Tri; Wuryandari, Yenny (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Streptomyces sp. and Trichoderma harzianum is a biological agent that is effective in controlling Colletotrichum capsici, the cause of disease in chili plants. Different growing media can affect the growth and activity of these two microorganisms. This study aims to evaluate the growth of Streptomyces sp. and Trichoderma harzianum on various media, namely rice washing water, coconut water, and sugar potato extract. The research phase includes growing media test, effectiveness test of Streptomyces sp. and Trichoderma harzianum in chili peppers, and effectiveness test of Streptomyces sp. and Trichoderma harzianum on chili seeds. The results showed that the medium of rice washing water is more suitable for Streptomyces sp., coconut water media is more suitable for Trichoderma harzianum, and rice washing water media is more suitable for the combination of the two biological agents. Optimal growth in these media affect the effectiveness of biocontrol in suppressing the severity of anthracnose disease in chili.